Penyelesaian Persamaan Diferensial Fraksional Riccati menggunakan Teorema Gabungan Adomian Laplace - Muhamad Deni Johansyah; Salma Az-Zahra (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2022)
Judging from the function or rank, differential equations can be divided into two, namely linear and nonlinear differential equations. Differential equations generally have the order of natural numbers, but differential equations can be further developed into fractional order form. A differential equation that has the order of fractional is called a Fractional Differential Equations (FDE). One form of nonlinear FDEs is Riccati's FDEs. Many researchers have researched Riccati's FDEs approximation using various methods. One method or two methods combined. In this research, the solution to Riccati FDEs will be search using the Combined Theorem of the Adomian decomposition method and the Laplace transformation (Adomian Laplace). Next, a graphic of Riccati PDF solutions is created using the Adomian Lapalce Combined Theorem and exact solutions, resulting graphs that coincide with each other.